Transforming nursing education through caring pedagogy: A systematic review of the experiential learning approach - Priyantini, Dwi; Hafizah Che Hassan (KHD-Production, 2026)
The increasing complexity of healthcare demands nursing education that effectively bridges the theory-practice gap while cultivating caring competence and professionalism. Traditional didactic methods often fail to adequately prepare students for clinical realities, necessitating a shift toward innovative pedagogical strategies. This systematic review evaluates the effectiveness of caring pedagogy and experiential learning approaches in transforming nursing education outcomes. Following the PRISMA 2020 guidelines, a comprehensive search was conducted across Scopus, PubMed, and ProQuest for studies published between 2022 and 2026. Methodological quality was appraised using the Joanna Briggs Institute (JBI) critical appraisal tools specific to each study design. From 250,393 identified records, 11 studies met the inclusion criteria. The included studies comprised seven randomized controlled trials, two quasi-experimental studies, one prospective cohort study, and one non-equivalent control group study. Quality appraisal rated three studies as high, seven as moderate, and one as low-moderate. Interventions included simulation-based learning, problem-based learning, role-play, peer education, and structured training programs. Synthesis of findings demonstrated significant improvements in professional competence, communication skills, psychomotor skills, critical thinking, self-efficacy, creativity, and patient safety adherence among nursing students and nurses. Caring pedagogy and experiential learning approaches are effective strategies for enhancing nursing competence and professionalism. Educational institutions should integrate these evidence-based interventions into curricula to better prepare nurses for contemporary healthcare challenges and ensure a workforce capable of delivering compassionate, high-quality care.